Macro-Policy Goals in the Postwar Period: Reply - Friedlaender, Ann F. (Quarterly Journal of Economics, 1975)
Journal Article Macro-Policy Goals in the Postwar Period: Reply Get access Ann F. Fhiedlaender Ann F. Fhiedlaender Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 89, Issue 4, November 1975, Pages 677–678, https://doi.org/10.2307/1884705 Published: 01 November 1975